Analisis Foto Jurnalistik Karya Aji Yk Putra (Studi Pada Pemberitaan kompas.com: Kisah Penyelam Pemburu Harta Karun Di Sungai Musi) - Firdaus , Muhamad; Syarifudin , Achmad; Muslimin, Muslimin (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This research is entitled Analysis of Photojournalism by Aji YK Putra (Study on Kompas.com Reporting: The Story of Treasure Hunter Divers in the Musi River) with the aim of the research to tell the public how the procession of searching for treasure in the bottom of the Musi River includes what items are obtained during the hunt and equipment used by divers when searching for treasure. Photojournalism is a visual work that displays a message through an image based on facts without engineering. The Musi River has a depth of 12 to 30 meters with a target for hunters, namely at a depth of 30 meters. The Musi River treasure hunters are a group of people who depend on their prey for what they get. Aji YK Putra as a photo reporter did in-depth coverage of a group of hunters on the Musi River so that they got some data about how dangerous hunting is carried out by divers by risking their lives on a breathing apparatus assembled from a compressor hose. From the data studied through Roland Barthes' semiotics, several research results were obtained which described the field conditions of hunters when diving in the depths of the Musi River. This research also proves that journalistic photo products are able to express objectivity towards an event that exists in society because the photo displayed is an image with a million meanings.